Two cases of pancreaticoduodenal aneurysm with median arcuate ligament syndrome treated with coil embolization and median arcuate ligament incision - Yoshiki Endo, MD; Hirofumi Sekino, MD, PhD; Shiro Ishii, MD, Ph.D.; Ryo Okada, MD, PhD; Yasuhide Kofunato, MD, PhD; Hiroshi Nakano, MD, PhD; Yohei Watanabe, MD, PhD; Shigeru Marubashi, MD, PhD; Koji Kono, MD, PhD; Hiroshi Ito, MD, PhD (Radiology Case Reports, 2022)
Median arcuate ligament syndrome is a clinical condition in which the median arcuate ligament causes compression and narrowing of the celiac artery. It has been reported that collateral pathways, which is developed by the decrease of blood flow from the celiac artery, facilitates the formation of aneurysms. Aneurysms around the pancreas in particular require aggressive therapeutic intervention, because a rupture can be fatal. We herein report two cases of pancreaticoduodenal aneurysms associated with median arcuate ligament syndrome treated by coil embolization and median arcuate ligament incision. Case 1 required a hybrid procedure in which median arcuate ligament incision and coil embolization were performed simultaneously. In Case 2, the median arcuate ligament incision was performed about 3 months after emergency endovascular hemostasis for hemorrhagic duodenal ulcer. In both cases, there were no major postoperative complications and no recurrence of aneurysm. Median arcuate ligament incision may be effective to prevent organ ischemia and aneurysm recurrence after coil embolization of intra-abdominal aneurysms associated with median arcuate ligament syndrome.